Molecular mechanism of influence of clay mineral types on coal mechanical heterogeneity - Bin ZHANG; Beilei SUN; Dezhang WANG; Tianhe KANG; Zhijie FENG; Ligong LI; Haoyang LI; Xiaomin LIANG; Wenqing ZHU; Junshuang ZHANG (Meitan xuebao)
Coalbed methane is an important unconventional natural gas resource in China, but coal reservoirs under the influence of inorganic minerals have strong mechanical heterogeneity, and there are situations where successfully used engineering technologies are not applicable to other coalbed methane wells. In depth research on the interaction between inorganic minerals and organic matter in coal and their impact on coal mechanical heterogeneity is of great significance. Molecular simulation was used to compare and analyze the interaction range, location, strength, and differences between three typical clay minerals, kaolinite, illite, and montmorillonite, and anthracite organic matter. The influence of different clay minerals on coal porosity was elucidated, and the response characteristics of coal mechanical heterogeneity to clay mineral types were revealed. The results showed that the radial distribution function of kaolinite or illite with coal organic matter exhibited a bimodal characteristic, with both hydrogen bonding and van der Waals forces present. In contrast, the radial distribution function of montmorillonite showed a unimodal distribution, with van der Waals forces being the main interaction, accounting for 89.36% of the total energy change, and no hydrogen bonding was observed; After entering the organic matter of coal, mineral molecules will stack and fill each other, forming a nano pore structure with certain heterogeneity and irregular shape. Under the same mineral content, the pore size order of coal containing different mineral types is: montmorillonite > illite > kaolinite; The strength of the interaction between clay minerals and coal organic matter mainly depends on the size of clay mineral molecules, which is inversely proportional; Under different kaolin contents, the heterogeneity of the bulk modulus, elastic modulus, and shear modulus of smokeless coal can be divided into five parts, with areas of extremely high variability. However, smokeless coal containing illite and montmorillonite, except for areas of high variability in shear modulus, all other mechanical parameters are below the low variability range. The influence of kaolin on the mechanical heterogeneity of smokeless coal is greater than that of illite and montmorillonite. The research results will provide a mechanical basis for predicting the changes in the mechanical properties of coal reservoirs and developing targeted reservoir modification measures and development plans based on the characteristics of different clay minerals in coal.